KARAKTERISTIK FOOT SALT SEBAGAI RELAKSASI DI MASA PANDEMI - Ratih Yuniastri; Dyah Ayu Fajarianingtyas; Eko Adi Sumitro (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2022)
Salt is a crystalline solid resulting from the evaporation of seawater which has many benefits both as food and as health and beauty products. The process of salt production by coastal communities still uses traditional methods and is marketed in the form of krosok salt. The use of krosok salt as a value-added health product can increase the income of coastal communities. One of them is in the form of foot salt. In this new normal era, foot salt products can be used to increase relaxation which can have an impact on the body's immunity. The preference test for several foot salt products is the goal of this research. The method used was a completely randomized design with 3 replications, then the samples were coded F1, F2, F3, F4, and F5. The panelists used were 30 women with a certain age range, namely 10 women aged 18-32 years, 10 women aged 33-46 years, and 10 women aged 47-60 years. Furthermore, the panelists were asked to use foot salt products for approximately 2 months in a row. Data obtained through hedonic tests and interviews. The resulting data were analyzed descriptively and quantitatively using Anova with Duncan's follow-up test. The results of the organoleptic test showed that the best sample for color parameters was F5; texture parameters are F4 and F5; and the appearance parameter is F5. In general, the panelists preferred the aroma of grapefruit and lavender with a smooth texture.